How do parents perceive and utilize knowledge of their infant's mental health? A systematic review. (June 2019) - Peters, Jane; Skirton, H; Morgan, J; Clark, M
Infant mental health (IMH) is a growing area of practice for health, education and social care practitioners, as links are increasingly made between experiences in the early years and subsequent child development, mental health and well-being. It is unclear how parents perceive IMH and use knowledge relating to IMH with their children. We conducted a systematic review, the aim of which was to determine parents' perceptions of IMH and how they utilize this knowledge with their infants. We undertook a search of relevant databases and journals and from an initial list of 4147 potential papers, identified 16 for the review. Original data were extracted and presented in a table, and the content of all papers was analysed thematically and presented in narrative form. Three main themes emerged from the available research: knowledge and understanding of child development, influences of society and culture, and interpretation of emotions and expressions. Our results indicate that research is limited in terms of parental perspectives of IMH and how they obtain and use this knowledge. Further research is needed to investigate this topic to maximize mental well-being in infancy and later life.